CCAFS Country Programs and Partnerships to Deliver Results - Kinyangi, James (International Livestock Research Institute, 2015)
Presented by James Kinyangi (CCAFS Regional Program Leader - East Africa) at GFIA 2015, Abu Dhabi, UAE. James spoke on the Kenyan example of a decision support tool to target Climate-Smart Agriculture investments. The take homes from the presentation focused on: Problem structuring & complexity reduction; Spatial indices built on consensus & evidence; Transferability & flexibility.